(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The aim of the research was to know the degree of availability of the strategic pillars of the human capacity development program to prepare a globally competitive citizen in the content of the social studies book for the first intermediate grade. To achieve this goal, the researchers prepared a content analysis tool that included (3) strategic pillars under which (74) sub-axes fall to prepare a globally competitive citizen. To ensure its validity, it was presented to a group of specialized arbitrators. The stability of the analysis tool was also calculated by analyzing the same material twice, and at two separate periods. The results of the first researcher’s analysis were compared with the results of the second researcher. The Holsiti equation was used to calculate this, and the average stability coefficient value was (0.93). The analysis results indicated that the number of sub-axes included in the book amounted to (42) sub-axes to prepare a globally competitive citizen at a rate of (58.3%) with different inclusion rates, as the first pillar (developing a solid and flexible educational foundation for all) obtained the highest inclusion rate (39.64%), followed by the third pillar (providing lifelong learning opportunities) at a rate of (17.82%), and it obtained The second pillar (preparing for the future labor market locally and globally) had the lowest inclusion rate (10.28%).